The tumor necrosis factor α (-308 A/G) polymorphism is associated with cystic fibrosis in Mexican patients - Sánchez Domínguez, Celia Nohemí; Reyes López, Miguel A.; Bustamante, Adriana; Cerda Flores, Ricardo Martín; Villalobos Torres, María del Carmen; Gallardo Blanco, Hugo Leonid; Rojas Martínez, Augusto; Martínez Rodríguez, Herminia Guadalupe; Barrera Saldaña, Hugo Alberto; Ortiz López, Rocío (Public Library of Science, 2014)
Environmental and genetic factors may modify or contribute to the phenotypic differences observed in multigenic and monogenic diseases, such as cystic fibrosis (CF). An analysis of modifier genes can be helpful for estimating patient prognosis and directing preventive care. The aim of this study is to determine the association between seven genetic variants of four modifier genes and CF by comparing their corresponding allelic and genotypic frequencies in CF patients (n = 81) and control subjects (n = 104). Genetic variants of MBL2 exon 1 (A, B, C and D), the IL-8 promoter (2251 A/T), the TNFa promoter (TNF1/TNF2), and SERPINA1 (PI*Z and PI*S) were tested in CF patients and control subjects from northeastern Mexico by PCR-RFLP. Results: The TNF2 allele (P = 0.012, OR 3.43, 95% CI 1.25–9.38) was significantly associated with CF under the dominant and additive models but was not associated with CF under the recessive model. This association remained statistically significant after adjusting for multiple tests using the Bonferroni correction (P = 0.0482). The other tested variants and genotypes did not show any association with the disease. Conclusion: An analysis of seven genetic variants of four modifier genes showed that one variant, the TNF2 allele, appears to be significantly associated with CF in Mexican patients.